Comprehensive feasibility investigation of river source heat pump systems in terms of life cycle. (April 2021) - Jung, Yujun; Kim, Joonbyum; Kim, Heejoon; Yun, Rin; Park, Changyong; Nam, Yujin; Cho, Honghyun; Lee, Hoseong
Highlights: Comprehensive feasibility of RSHP systems is investigated in terms of life cycle. Thermal potential of river water can satisfy 23% of the building energy demand in Seoul. Energy consumption and CO2 emissions are reduced by 16.4% and 10.5%, respectively. Important factors to improve the RSHP system are hydronics and water body temperature. Abstract: In this study, the feasibility of thermal energy utilization in river source was comprehensively investigated by separately estimating the thermal potential of river source and evaluating the performance of a river source heat pump system. First, the thermal potential of a river water body was calculated by measuring the water temperature and flow rate. The annual natural potential, geographical potential, technical potential, and practical potential were estimated as 68, 883, 64, 045, 61, 291, and 17, 634 TJ/yr, respectively. An analysis of the practical potential of the river showed that it can sufficiently satisfy 23% of the building demand in Seoul. Second, the performance of the river source heat pump system was evaluated in terms of its life cycle performance, considering energetic, environmental, and economic metrics. When the river source heat pump system was applied to office building, the energy consumption and CO2 emissions were reduced by 6.9% and 10.5%, respectively. The results of the economic feasibility study presented a net present value of $10, 587, 848, an internal rate of return of 20.5%, and a payback period of 5.3 years. In addition, a parametric study showed the maximum improvement of the energy consumption, CO2 emissions, and economics are expected to be 16.4%, 19.6%, and 15.2%, respectively.